Why Was Keynes Not Awarded the Nobel Peace Prize After Writing "The Economic Consequences of the Peace"? - Lars Jonung (Lund University, School of Economics and Management, Department of Economics, 2021)
John Maynard Keynes became world famous with the publication of The Economic Consequences of the Peace in 1919, a harsh critique of the Versailles peace treaty. As a consequence, Keynes was nominated by German professors in economics for the Nobel Peace Prize three years in a row, 1922, 1923 and 1924. Because Keynes was put on the shortlist of candidates, he was evaluated in an advisory report in 1923, followed by one in 1924, prepared for the Nobel Committee of the Norwegian parliament. This paper summarizes the two reports on Keynes. The appraisals were highly appreciative of Keynes's book as well as of his subsequent newspaper and journal articles on the peace treaty, raising the question: why did Keynes not receive the Peace Prize? The appraiser of Keynes even informed Keynes that he was "one of the foremost candidates proposed for the Nobel Peace Prize." However, the Peace Prize was not awarded in 1923 and 1924 although Keynes was declared a worthy laureate. There are no protocols that shed light on this issue. Still, the events surrounding the evaluation process, in particular the public clash between two advisors of the Prize Committee on Keynes's account of the negotiations at Versailles, encourage a speculative answer.
Keywords: A11; B10; B31; D70; E12; E60; F30; F50; N10; N40; 330; John Maynard Keynes; Nobel Peace Prize; Treaty of Versailles; reparations; Dawes Plan; Bretton Woods; Norway